Взаємозв’язок критеріїв теплового стану горна з газодинамікою процесу і характеристиками продуктів доменної плавки - Кузнецов, Максим; Крячко, Геннадій (Physico-technological Institute of Metals and Alloys, 2023)
The article analyzes the suitability of the known operating criteria of the blast-furnace operation for assessing the influence of the iron receiver thermal state on gas dynamics of the process and the characteristics of smelting products. The operation of two blast furnaces with the volume of 1500 and 1386 m3 in different periods from 2015 to 2020 was investigated. Taking into account the dependence of the degree of silicon reduction and gas dynamic processes on the pressure in the working space of the furnace, the choice of the studied periods was carried out proceeding from the condition of fluctuations in the gas pressure on the furnace top within the limits not exceeding 5 kPa. It has been confirmed that the ratio of the theoretical temperature of combustion and the temperature of cast iron at the outlet, as well as the difference of these temperatures, can be used as indicators of the thermal state of the iron receiver, such as those that, firstly, are directly related to the bottom of the blast furnace and, secondly, they have a fairly close connection with the derivatives of the process, namely, gas dynamics and properties of smelting products. It was found that the use of the ТT/ti ratio has an advantage, since it has a closer relationship with the parameters of the blast furnace process than the difference between the above temperatures. The data showing the advantage of the TT/ti criterion in comparison with the theoretical combustion temperature for the operational control of the thermal state of the iron receiver (hearth) are shown. It has been established that, depending on the state of the furnace, raw material and operating conditions, and the range of change in ТT/ti, an increase in the latter ratio can affect the lower pressure drop in different ways. It is shown that with an increase in the value of the criterion ТT/ti, the temperature of the cast iron decreases. It is explained how the blast mode, estimated by the theoretical combustion temperature, can affect the formation of the final slag and pig iron at the outlet, namely through the competitive development of endothermic reactions of direct reduction and desulfurization of pig iron. In contrast to the dependencies of the temperature of cast iron on changes in the criterion ТT/ti, no significant relationship was found between this criterion and the silicon content in cast iron [Si]. The data obtained once again indicate the lack of reliability [Si] as a criterion for the thermal state of the iron receiver (hearth).